Outdoor recreation activities: How do they affect students’ physical fitness and mental health? - Tajuddin, Al Ihzan; Fufu, Ronald Dwi Ardian; Wijaya, I Nyoman Wahyu Esa; Neolaka, Erwin Sarnoto; Louk, Michael Johannes Hadiwijaya (Tanjungpura Journal of Coaching Research, 2026)
Background Declining physical activity and increasing mental health problems among university students have become major public health concerns. Although outdoor recreation has been associated with physical and psychological benefits, evidence regarding the effectiveness of structured outbound recreation in improving both physical fitness and mental health among university students remains limited. Objectives This study aimed to examine the effect of outbound recreation on the physical fitness and mental health of fifth-semester students enrolled in the Physical Education. Methods This study employed an experimental method using a one-group pretest–posttest design involving all research participants. This study was conducted in the Physical Education, Health, and Recreation Program, Faculty of Teacher Education and Educational Sciences, Nusa Cendana University, with 38 students. Physical fitness was assessed using an appropriate standardized physical fitness test, while mental health was measured using a standardized questionnaire. The collected data were analyzed using descriptive statistics and inferential statistics through a paired-samples t-test at a significance level of 0.05. Results The findings revealed that the outbound recreation program significantly improved the students' physical fitness and mental health (p = 0.000). Improvements in mental health were observed across several dimensions, including emotional well-being (75%), psychological well-being (73%), self-control (76%), and life satisfaction and happiness (77%), all of which were classified as being in the strong category. Meanwhile, the dimensions of social well-being as well as adaptation and resilience demonstrated improvements within the moderate category. These findings indicate that outbound recreation is an effective approach for enhancing both the physical fitness and mental health of university students. Conclusion Structured outbound recreation is an effective recreation-based learning strategy for enhancing university students' physical fitness and mental health. These findings provide empirical evidence supporting the integration of outdoor recreation into higher education programs to promote student well-being through experiential learning and physical activity.